Governing queer histories and futures: a critical place-based analysis of state apology - Albion, Astrid (Critical criminology, 2022)
The southern island of Tasmania is renowned for being the last Australian state to decriminalise homosexuality in 1997. Twenty years after the repeal of these laws, the state parliament of Tasmania passed legislation introducing an expungement scheme for historical homosexual convictions and delivered an apology for their harms. In this article, we draw upon theories of sexual citizenship to develop a critical place-based analysis of the Tasmanian apology that is attentive to the specificities of the region’s political, social, and cultural context. We argue that the parliament’s attempts to redefine the boundaries of sexual belonging through apology and expungement entail new forms of erasure, exclusion and policing. The limits of the apology’s liberal discourse of progress are foretold by several tendencies within its narration, including: the persistent impulse to erase both past records of the law’s violence and future LGBTQIA + identities; assumptions of sexual essentialism and biological determinism; and the uneasy demarcation of il/legal sexual practices, which reasserts the state’s authority to govern sexuality through recourse to the criminal law. Our analysis highlights the need for more place-based analysis of emergent modes of sexual governance within queer criminology and for further research into the material benefits, if any, that apologies and expungement schemes provide to those affected.